An Evidenced-Based Review of Emergency Target Blood Pressure Management for Acute Aortic Dissection - Hankui Hu; Zhoupeng Wu (Emergency Medicine International)
Objective. To summarize the best evidence of emergency target blood pressure management for acute aortic dissection and provide guidance for evidence-based practice of emergency target blood pressure management. Methods. According to the “6S” evidence pyramid model, the evidence of emergency target blood pressure management of acute aortic dissection in various foreign databases and websites of professional associations from January 1, 2010, to August 1, 2022, was retrieved, including clinical decision-making, guidelines, expert consensus, systematic reviews, randomized controlled trials, cohort studies, and case series. Two researchers used the corresponding document quality evaluation tools to evaluate the documents and extracted and summarized the evidence of documents above grade B. Results. A total of 17 articles were included, including 6 clinical decision-making articles, 5 guidelines, 2 expert consensus articles, 1 systematic review article, 1 randomized controlled trial article, 1 cohort study article, and 1 case series article, forming 36 best evidences, including 9 topics, which are target value setting, management strategy, disease observation, medical history collection, monitoring methods, vasoactive drugs, nonvasoactive drugs, related examinations, and patient education. Conclusion. The best evidence summarized provides a reference for doctors and nurses in the emergency department to manage the emergency target blood pressure of patients with acute aortic dissection. It is recommended that doctors and nurses in the emergency department follow the best evidence summarized to develop individualized target blood pressure management plan for patients.